Association Between Neonatal Arrhythmia and Mortality and Recurrence: A Retrospective Study - Ran, Lihong; Li, Jie; Bao, Lei; Chen, Long (Frontiers in Pediatrics, 2022)
Objective The aim of the present study was to explore the association between neonatal arrhythmia (NA) and mortality and recurrence. Methods A single-center, retrospective study was performed between January 1, 2015, and December 31, 2019. Neonates with NA were eligible and divided into either benign or non-benign groups. The primary outcomes were mortality and recurrence within 2 to 6 years. Results NA was diagnosed in 189 patients (0.39%) after screening 47,911 hospitalized neonates, and 10 of them did not finish the follow-up. Finally, 179 neonates were included into the final analysis (58 in the non-benign NA and 121 in the benign NA groups). The incidences of death and recurrence for NA were 5.59% (10/179) and 18.44% (33/179). Compared with neonates with benign NA, those neonates with non-benign NA were shown higher rates of death (13.79% vs. 1.65%; odds ratio [OR], 5.73; 95% confidence interval [CI], 1.07–31.01; p = 0.04) and recurrence (44.83% vs. 5.79%; OR, 8.49; 95% CI, 3.12–23.08; p < 0.001). Conclusions Neonates with non-benign NA were shown higher rates of death and recurrence when compared with benign NA. Because of high recurrence, more attention was needed in neonates with non-benign NA after discharge.